A new species of Huntemannia (Copepoda: Harpacticoida: Huntemanniidae) from the Yellow Sea, Korea - Song, Sung Joon; Rho, Hyun Soo; Kim, Won (Zootaxa, 2007)
Huntemannia doheoni sp. nov. is described from a muddy sand flat off the coast of the Yellow Sea, Korea. The new species can be distinguished from its congeners by a combination of characters that include: a strong, hook-like outer process on the P1 coxa; incompletely fused exopod segments and reduced setal formulae of the P2–P4 in the female; and modified outermost spine on the distal segment of P3–P4 in the male. In addition, a key to the species of Huntemannia is provided.